Back Cover. (29th April 2020) - Luo, Zhongxia; Zhang, Xiongjian; Chen, Jingyi; Wang, Zhangying; Huang, Lifei; Zou, Hongda; Yao, Zhufang; Yang, Yiling; Fang, Boping
Abstract : The cover image is based on the Original Article Examination and genetic analysis of a yellow‐green leaf mutant a269 of sweetpotato by Luo et al., https://doi.org/10.1111/pbr.12785 .